Bridging law, Business and Technology: The role of Industrial Property in University Curricula in Albania - Qoku, Maksim; Spiro, Lira (European Journal of Social Science Education and Research, 2025)
Industrial Property plays a pivotal role in fostering innovation and entrepreneurship, functioning both as a legal safeguard and an economic driver. This study examines the current integration of Industrial Property (IP) education within Albanian higher education, with the aim of identifying the extent to which university curricula respond to the needs of a knowledge-based economy. Methodologically, the research combines theoretical analysis with empirical data, drawing on interviews with academic staff and survey responses from students in Law, Economics and Engineering faculties across selected universities. The curricula are evaluated through a qualitative content analyss framework based on interdisciplinarity, theoretical-practical balance and professional skill development. Findings indicate strong consensus among professors and students regarding the relevance of IP for employability, creativity and innovation capacity. However, significant gaps emerge in curricular integration, institutional support and faculty specialization, resulting in limited preparedness for professional IP related contexts. The study argues that embedding IP into higher education should not be treated as a minor curricular addition but as a strategic investment in academic quality, innovation culture and national competitiveness. The proposed recommendations contribute to ongoing discussion on curriculum reform in emerging economies.